Analisis Morfologi pada Teks Bacaan “Malin Kundang” Karya Dini Ayu - Irawati, Wahyu; Raudhatunnur; Nugraheni, Aninditya Sri (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to analyze the morphology in the reading text "Malin Kundang" by Dini Ayu, which is an adaptation of a classical Indonesian legend. This research uses a qualitative approach with descriptive methods to identify and analyze morphological processes, including affixation, reduplication, and composition. The results of the analysis show that there are four types of affixation processes: (1) prefixation, (2) suffixation, (3) infixation, and (4) confixation, as well as the use of compound words and reduplication which enrich the language structure in the text. These findings provide insight into the linguistic creativity of authors and the contribution of morphological elements to the meaning and function of narrative in literary works. The research is expected to enrich the study of literary linguistics and provide recommendations for teaching language and literature in education.